REAKCJA WÓD POWIERZCHNIOWYCH I PODZIEMNYCH NA OPADY W ZLEWNI RÓŻANEGO STRUMIENIA - CZUCHAJ, ALEKSANDRA; WOLNY, FILIP; MARCINIAK, MAREK (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2019)
The aim of the presented research was to analyze the relation between three variables: the daily sum of precipitation, the surface water level and the groundwater level in the Różany Strumień basin located in Poznań, Poland. The correlation coefficient for the subsequent lags for each pair of variables time series has been calculated. The delay with which waters of the basin respond to precipitation varies significantly. Generally, stronger response to rainfall is observed for surface water levels as opposed to groundwater levels.